Wege aus dem Ego-Tunnel: zur gegenwärtigen Bedeutung der Phänomenologie - Fuchs, Thomas (Deutsche Zeitschrift für Philosophie, 2015)
Phenomenology may be considered the systematic science of subjective experience and its basic structures of intentionality, embodiment, temporality and intersubjectivity. Thus it is assigned the crucial task of defending subjective experience against reductionist claims raised by proponents of naturalism or physicalism. Nonetheless, phenomenology is far more than a mere science of consciousness which it maintains as an impregnable, but sterile citadel. On the contrary, as a science of embodied and extended subjectivity, it touches the fields of empirical sciences and enters with them into a productive dialogue. This is shown in three areas of science: (1) by the crucial role of phenomenology for the paradigm of embodied and extended mind in cognitive neuroscience; (2) by the phenomenological concept of primary social cognition as intercorporeality; and (3) by the phenomenological psychopathology of embodiment, in particular in schizophrenia.